Transformasi Digital Dalam Profesi Keguruan: Adaptasi dan Tantangan Guru di Era Artificial Intelligence - salsa bila; Nur Indah; salsabila lubis; Asla Alayya; Muhammad Hasyimsyah (Advances In Education Journal, 2026)
AI-driven digital transformation has significantly shifted the role of teachers from teacher-centered to learner-centered. Teachers now serve as facilitators, mediators, and learning designers who leverage AI technology through adaptive learning systems and real-time analysis of student data. However, the integration of AI in education faces various challenges, including the digital divide, limitations in teachers’ technological competencies, a lack of ongoing training, and ethical issues related to privacy and data security. Resistance to change is also a major barrier to technology adoption. The success of digital transformation in education requires comprehensive readiness, including the enhancement of teachers’ competencies, institutional support, and adaptive and ethical policies. Strategic efforts are needed to improve teachers’ digital literacy in order to create an educational ecosystem that supports the effective and responsible integration of technology.